Climate Change and Energy Dynamics in the Middle East Modeling and Simulation-Based Solutions - Qudrat-Ullah, Hassan; Kayal, Aymen A. (Understanding Complex Systems, 2019)
XII, 376 p. 166 illus., 150 illus. in color.